UPAYA PENCEGAHAN RADIKALISME SEJAK DINI MELALUI SOSIALISASI PENGUATAN MODERASI BERAGAMA PADA SISWA MADRASAH ISLAMIYAH DESA ANGIN BARAT, MANDAILING NATAL - Roni Risky Nasution; Nanang Arianto; Adam Maulana; Hamir Hamsah Dalimunte; Masroani Siregar; Siti Rukiah; Ummi Atikah; Hafizah Hapsani; Nurasiah Nurasiah; Riani Agustina (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This article discusses activities to strengthen religious moderation through socialization and education carried out by Group 41 Community Service Program (KKN) students from the Mandailing Natal State Islamic College at the Madrasah Islamiyah in Angin Barat Village, Mandailing Natal. This activity aims to increase students' understanding of the values of religious moderation and prevent the emergence of radicalism from an early age. The research used a qualitative approach with participatory methods through interactive lectures, group discussions, case studies, and role plays. A total of 35 male and female students from grades II, III, and IV were actively involved in the learning process. The results of the study showed a significant increase in cognitive aspects, as seen from the students' increased understanding of the concept of moderation, as well as affective changes in the form of more tolerant, inclusive, and critical attitudes towards digital content with radical potential. In addition, the role of teachers as facilitators and the emergence of peer learning initiatives among students were important factors in strengthening the internalization of moderate values. However, the limited duration of the implementation, which was only one day, and the simple learning tools limited the depth of the intervention. This study concludes that strengthening religious moderation based on participatory practices is effective as a preventive strategy against radicalism in madrasahs and needs to be integrated continuously into education programs.